New Trends for Securing Cybersecurity Data - Saba Alaa Abdulwahhab; Qasim Mohammed Hussein; Emad F. Taha (Journal of Madenat Alelem University College, 2022)
After most of the data has become widely transmitted in digital devices, which affects the security of this data due to a large number of hackers, and to protect it, encryption is used as one of the reliable methods to ensure data security. The important condition of the encryption system depended on time, amount of data, and cost of encryption.           However, the development in computational capabilities led to the thinking of a new type of cryptography is called quantum cryptography (QC), it is a technology that allows for quicker, more effective, and secure communication than the traditional way. so the term post-quantum cryptography (PQC) refers to the usage of a cryptographic method that is thought to be immune to quantum assaults. as a result, Quantum-era cybersecurity will be capable of detecting and deflecting quantum-era cyberattacks before they do harm using the most efficient algorithm, the study goal is to highlight developments in cryptography systems and compare them in time execution using the same amount of data.